Fidel: the Cuban doctors' paradigm - Raúl Joaquín Varela García (Centro Provincial de Información de Ciencias Médicas, 2017)
Documents related to the development of the Cuban public health after the victory of the Revolution and the help to other countries are reviewed. The Commander in Chief Fidel Castro Ruz direct participation is verified in many of the achievements reached byCubaregarding health and in the practice of the proletarian internationalism. Also, it is demonstrated that the revolutionary will of a man as Fidel could mobilize the human conscience for a better world.